Impact of Honeybee Venom Melittin on Cell Viability of Different Prostate Cancer Lineages - R. R. Khalikov; D. D. Gromenko; S. Sh. Galimova; K. V. Danilko; I. D. Gromenko; Sh. N. Galimov; P. F. Litvitsky (Креативная хирургия и онкология)
Background. Melittin is a major constituent of honeybee venom and comprises a water-soluble surfactant peptide with cytolytic effects potentially applicable in anticancer therapy. We evaluated the impact of melittin from Bashkir honeybee (Apis mellifera mellifera L.) venom on cell viability of various prostate cancer lineages.Materials and methods. MTT assays with cell viability index estimation were used to evaluate the effect of melittin on cell proliferation in various-grade malignancy prostate cancer (PC) lineages, LNCaP, PC-3 and DU145.Results and discussion. Lineage DU145 revealed a low sensitivity to melittin, because a relatively high peptide concentration of 10 μg/mL had a suppressive effect on its proliferation. With PC-3 cells, a 0.1 μg/mL concentration suppressed proliferation significantly to 46.15 %, while melittin at a 10 μg/mL dose had a cytolytic effect on most cells (4.27 % viability). LNCaP cells experienced the lowest toxicity at 10 μg/mL melittin compared to PC-3 and DU145 lineages. The LNCaP, PC-3 and DU145 PC lineages demonstrated suppressed proliferation at melittin levels 0.01–100 μg/mL.Conclusion. The study reveals a significant reduction of the PC lineages viability at a minimal melittin concentration of 0.01 μg/mL, which indicates a high cytolytic activity of this peptide and renders it a candidate agent in antitumour therapy.